The political context of AIDS-related stigma and knowledge in a South African township community - Brian Forsyth; Alain Vandormael; Trace Kershaw; Janis Grobbelaar (Taylor & Francis Group, 2008)
The purpose of this study was to examine the presentation of AIDS-related stigma and knowledge within the political context of the South African government's response to the AIDS epidemic. It was during the 2000 - 2004 period that key government officials publicly challenged the orthodox views of HIV/AIDS, with the South African president, Thabo Mbeki, actively positing the primary role of poverty and other socio-economic stressors in the progression of the AIDS epidemic. This discursive position had real-time effects for AIDS policy-making and ultimately delayed the implementation of a national antiretroviral (ARV) rollout programme. Consequently this position was criticised by commentators in the media and elsewhere for contributing to an already widespread climate of AIDS stigmatisation and misinformation. To shed more light on these claims we conducted a survey in 2005 in Atteridgeville, a South African township, and compared results with those of a similar survey conducted shortly after ARV medications became available in 2004. Results indicated a reduction in AIDS stigma levels across the 1-year period, and that those participants who endorsed contentious political views (such as those expressed by key government officials) were more likely to have a higher level of AIDS-related stigma than those who disagreed. Nevertheless, this study cautions against drawing a causal relationship between the South African government's position and AIDS-stigmatising attitudes, and suggests that further political and social factors be accounted for in an attempt to gain a fuller understanding of this seemingly complex relationship.